Q.19 Use the Factor Theorem to determine whether g (x) is a factor of p (x) in each of
the following cases
(i) p (x)= 2x3 +4 x2 - 2x - 1, g(x) = x - 1
(ii) p(x)= x3 + 3x2 + 3x + 10, g (x) = x-3
Answers
Answered by
2
Answer:
(i) Apply factor theorem
x+1=0
So x=−1
2x ^3 +x ^2 −2x−1
Replace x by −1, we get
2(−1) ^3 +(−1) ^2 −2(−1)−1=−2+1+2−1=0
Reminder is 0 so that x+1 is a factor of 2x ^3
+x ^2 −2x−1
(ii) Apply factor theorem
x+2=0
So x=−2
x -3 +3x -2+3x+1
Replace x by −2, we get
(−2)^3 +3(−2)^2 +3(−2)+1=−8+12−6+1=1
Reminder is 1 so that x+2 is not a factor of x -3
+3x^2 +3x+1
Similar questions